2022
DOI: 10.1111/cdev.13756
|View full text |Cite
|
Sign up to set email alerts
|

“So, like, it’s all a mix of one”: Intersecting contexts of adolescents’ ethnic‐racial socialization

Abstract: Cultural‐ecological theories posit that ethnic‐racial identity (ERI) development is shaped by transactions between contexts of ethnic‐racial socialization, yet research considering intersections among multiple contexts is limited. In this study, Black, Latino, White, and Asian American adolescents (N = 98; Mage = 16.26, SD = 1.09; 55.1% female identifying) participated in surveys and focus group discussions (2013–2014) to share insights into ERI development in context. Using consensual qualitative research, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…Adolescents are bombarded with messages regarding race and ethnicity on a daily basis in the multiple contexts in which they find themselves, including virtual and in-person experiences (Rivas-Drake & Umaña-Taylor, 2019). Youth regularly engage with messages related to race and ethnicity from media (e.g., movies, music, and social media), exchanges with their peers, interactions with their family, and experiences in society more broadly (e.g., Jones & Rogers, 2022; Sladek et al, 2022; Tynes et al, 2019). Thus, the salience of race and ethnicity for adolescents in the United States makes this an important social identity on which young people are focused and trying to understand as they are questioning and exploring their identities and trying to gain a sense of clarity regarding who they are who they can become.…”
Section: Ethnic-racial Identity Formation As a Developmental Competencymentioning
confidence: 99%
“…Adolescents are bombarded with messages regarding race and ethnicity on a daily basis in the multiple contexts in which they find themselves, including virtual and in-person experiences (Rivas-Drake & Umaña-Taylor, 2019). Youth regularly engage with messages related to race and ethnicity from media (e.g., movies, music, and social media), exchanges with their peers, interactions with their family, and experiences in society more broadly (e.g., Jones & Rogers, 2022; Sladek et al, 2022; Tynes et al, 2019). Thus, the salience of race and ethnicity for adolescents in the United States makes this an important social identity on which young people are focused and trying to understand as they are questioning and exploring their identities and trying to gain a sense of clarity regarding who they are who they can become.…”
Section: Ethnic-racial Identity Formation As a Developmental Competencymentioning
confidence: 99%
“…The study identified processes that have been established by the existing ERS literature, such as discussing ethnic/racial issues, having ethnic food, and engaging in cultural activities together with peers. However, the study also identified processes that are unique to peer groups, such as affiliating with peers from same‐ and diverse ethnic/racial groups, learning about peers' ethnic/racial identity and attitudes, and interacting with peers on social media (Sladek et al, 2022). These processes have not yet been captured by existing peer ERS measures or quantitative research, suggesting that more work is needed to systematically investigate the construct of peer ERS.…”
Section: Conceptualizing Peer Ethnic/racial Socializationmentioning
confidence: 99%
“…Beyond the question of what peers are doing around issues of ethnicity/race, another key issue for understanding peer ERS is to identify who actually performs these socialization practices. The existing research has considered peers in a relatively aggregated form, either asking participants to reflect on ERS from peers generally (Golden et al, 2021; Nelson et al, 2018; Sladek et al, 2022) or from their friends (Chen et al, 2020; Lesane‐Brown et al, 2005; Su et al, 2020; Wang et al, 2015). Below, we highlight a few peer characteristics that may be important to consider when examining the nature of peer ERS and its influence on adolescent outcomes.…”
Section: Identifying the Agents Of Peer Ethnic/racial Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, most studies examining ethnic-racial socialization have focused on parents; however, adolescents spend a significant amount of time in school and tend to gravitate toward school adults (e.g., teachers, coaches) for socio-emotional support (Roeser et al, 2000). Hence, school adults may represent additional agents of ethnic-racial socialization (Byrd, 2015; Sladek et al, 2022).…”
mentioning
confidence: 99%